Ferritic alloys
By optimizing the content relationship between Cr, Si and Al in ferrite alloy, a protective surface layer with aluminum-rich oxide is formed, which solves the problem that it is difficult for the alloy to form a protective oxide layer at low temperatures, and achieves good oxidation resistance and ductility.
Patent Information
- Application Number
- CN201780091046.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2017-05-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2037-05-24
AI Technical Summary
It is difficult for the existing ferrite alloy to form a protective α-alumina layer at a temperature below 900°C, resulting in corrosion and embrittlement problems.
By optimizing the composition of the alloy, it is ensured that the contents of Cr, Si and Al meet a specific equation (0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022) is met to promote the formation of a protective surface layer with an aluminum-rich oxide.
A ferrite alloy with excellent oxidation resistance and ductility at a temperature below 900°C is achieved, reducing brittleness and increasing high temperature corrosion resistance is achieved.
Smart Images

Figure BPA0000281095740000093 
Figure BPA0000281095740000101 
Figure BPA0000281095740000111
Abstract
Description
Technical Field
[0001] The present disclosure relates to a ferritic alloy as described in the preamble of claim 1. The present disclosure also relates to the use of the ferritic alloy and to articles or coatings produced therefrom. Background Art
[0002] Ferritic alloys, such as FeCrAl alloys containing 15-25 wt. % chromium (Cr) and 3-6 wt. % aluminum (Al), are well known for their ability to form protective α-aluminum oxide (Al2O3) when subjected to temperatures between 900° C. and 1300° C. 2 O 3 ), alumina, scale. The lower limit of Al content to form and maintain alumina scale varies with contact conditions. However, at higher temperatures, the impact of too low Al content levels is that the selective oxidation of Al will fail and a less stable and less protective chromium and iron based scale will be formed.
[0003] It is generally accepted that FeCrAl alloys generally do not form a protective alpha-alumina layer if subjected to temperatures below about 900° C. Several attempts have been made to optimize the composition of FeCrAl alloys so that they will form protective alpha-alumina at temperatures below about 900° C. However, these attempts have not been very successful overall, since the diffusion of oxygen and aluminum to the oxide-metal interface is relatively slow at lower temperatures, resulting in a lower rate of aluminum oxide scale formation, which means that there is a risk of severe corrosive attack and the formation of a less stable oxide.
[0004] Another problem that arises at lower temperatures, i.e., temperatures below 900°C, is the long-term embrittlement phenomenon caused by the low-temperature miscibility gap of Cr in the FeCrAl alloy system. At 550°C, a miscibility gap exists above about 12 wt. % Cr. Recently, alloys with lower Cr contents of about 10-12 wt. % Cr have been developed to avoid this phenomenon. It has been found that such alloys have good thermal stability under controlled and low-pressure O 2 It performs very well in molten lead.
[0005] EP 0 475 420 relates to a rapidly solidified ferritic alloy foil consisting essentially of: Cr, Al, about 1.5-3 wt. % Si, and REM (Y, Ce, La, Pr, Nd), the balance being Fe and impurities. The foil may also contain about 0.001-0.5 wt. % of at least one element selected from Ti, Nb, Zr and V. The foil has a grain size of no greater than about 10 μm. EP 075 420 discusses the addition of Si to improve the flow characteristics of the alloy melt, but with limited success due to reduced ductility.
[0006] EP 0091 526 relates to alloys which are resistant to heat cycle oxidation and which are hot workable, and more particularly to iron-chromium-aluminium alloys containing rare earth additions. In oxidation, the alloys will produce the whisker texture oxides which are desirable on the surfaces of catalytic converters. However, the resulting alloys do not provide high temperature resistance.
[0007] Therefore, there is still a need to further improve the corrosion resistance of ferritic alloys so that they can be used in corrosive environments during high temperature conditions. An aspect of the present disclosure is to solve or at least reduce the above problems. Summary of the invention
[0008] Thus, the present disclosure is directed to a ferritic alloy that will provide a combination of good oxidation resistance and excellent ductility, the ferritic alloy comprising the following composition in weight % (wt %):
[0009] C 0.01 to 0.1;
[0010] N: 0.001-0.1;
[0011] O: ≤0.2;
[0012] Cr 4 to 15;
[0013] Al 2 to 6;
[0014] Si 0.5 to 3;
[0015] Mn: ≤0.4;
[0016] Mo+W≤4;
[0017] Y≤1.0;
[0018] Sc, Ce, La and / or Yb≤0.2;
[0019] Zr≤0.40;
[0020] RE≤3.0;
[0021] The balance is Fe and commonly occurring impurities and must also satisfy the following equation:
[0022] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022.
[0023] Thus, there is a relationship between the contents of Cr and Si and Al in the alloy according to the present disclosure, which, if satisfied, will provide an alloy having excellent oxidation resistance and ductility as well as reduced brittleness and increased high temperature corrosion resistance.
[0024] The present disclosure also relates to an article and / or a coating comprising a ferritic alloy according to the present disclosure.In addition, the present disclosure also relates to the use of a ferritic alloy as defined above or below for the manufacture of an article and / or a coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1a and Figure 1b The phase diagram of Fe-10%Cr-5%Al relative to Si content is disclosed ( Figure 1a ) and the phase diagram of Fe-20%Cr-5%Al relative to Si content ( Figure 1b ). This figure was produced by using the database TCFE7 and the Thermocalc software.
[0026] Figure 2a to Figure 2e Comparison of polished cross-sections of two alloys according to the present disclosure and three reference alloys after exposure to biomass (wood chip) ash containing a large amount of potassium at 850°C and subjected to 50 one-hour cycles is disclosed. DETAILED DESCRIPTION
[0027] As mentioned above, the present disclosure provides a ferrite alloy, which comprises, in terms of weight % (wt %):
[0028] C 0.01 to 0.1;
[0029] N: 0.001-0.1;
[0030] O: ≤0.2;
[0031] Cr 4 to 15;
[0032] Al 2 to 6;
[0033] Si 0.5 to 3;
[0034] Mn: ≤0.4;
[0035] Mo+W≤4;
[0036] Y≤1.0;
[0037] Sc, Ce, La and / or Yb≤0.2;
[0038] Zr≤0.40;
[0039] RE≤3.0;
[0040] The balance is Fe and commonly occurring impurities and must also satisfy the following equation:
[0041] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022.
[0042] It has been surprisingly found that alloys as defined above or below, i.e. alloys containing said alloying elements and within the ranges mentioned herein, unexpectedly form a protective surface layer containing aluminum-rich oxides even when the chromium content is as low as 4% by weight. This is very important for the workability and long-term phase stability of the alloy, because after prolonged exposure to the temperature range mentioned herein, the undesirable brittle σ phase will be reduced or even avoided. Therefore, the interaction between Si and Al and Cr will promote the formation of a stable and continuous protective surface layer containing aluminum-rich oxides, and by using the above equation, Si can be added and still obtain a ferritic alloy that can be produced and formed into different articles. The inventors have surprisingly found that if the amounts of Si and Al and Cr are balanced so that the following conditions are met (all numbers of elements are weight fractions):
[0043] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022,
[0044] The resulting alloy will then have a combination of excellent oxidation resistance and workability and formability within the Cr range of the present disclosure. According to one embodiment, 0.015≤(Al+0.5Si)(Cr+10Si+0.1)≤0.021, such as 0.016≤(Al+0.5Si)(Cr+10Si+0.1)≤0.020, such as 0.017≤(Al+0.5Si)(Cr+10Si+0.1)≤0.019.
[0045] The ferritic alloys of the present disclosure are particularly useful for temperatures below about 900°C, since a protective surface layer containing aluminum-rich oxides will be formed on articles and / or coatings made from the alloys, which will prevent corrosion, oxidation, and embrittlement of the articles and / or coatings. In addition, the ferritic alloys of the present disclosure can provide protection against corrosion, oxidation, and embrittlement at temperatures as low as 400°C, since a protective surface layer containing aluminum-rich oxides will be formed on the surface of articles and / or coatings made therefrom. In addition, the alloys according to the present disclosure will also perform well at temperatures up to about 1100°C, and they show a reduced tendency to long-term embrittlement in the temperature range of 400 to 600°C.
[0046] The alloys of the present disclosure can be used in the form of a coating. In addition, articles may also contain the alloys of the present disclosure. According to the present disclosure, the term "coating" is intended to refer to the following embodiments: wherein the ferritic alloy according to the present disclosure is present in the form of a layer, which is placed in a corrosive environment in contact with a substrate, regardless of the means and methods for achieving it, and regardless of the relative thickness relationship between the layer and the substrate. Thus, examples thereof are, but are not limited to, PVD coatings, overlays, or compounds or composite materials. The purpose of the alloy should be to protect the underlying material from corrosion and oxidation. Examples of suitable articles are, but are not limited to, composite pipes, tubes, boilers, gas turbine components, and steam turbine components. Other examples include superheaters, water-cooled walls in power plants, containers or heat exchangers (e.g., for hydrocarbons or CO / CO 2 Components used in the reforming or other treatment of gases, components used in connection with industrial heat treatment of steel and aluminum, powder metallurgy processes, gas and electric heating elements.
[0047] In addition, the alloys according to the present disclosure are suitable for use in environments with corrosive conditions. Examples of such environments include, but are not limited to, contact with salts, liquid lead and other metals, contact with ash or high carbon content deposits, combustion atmospheres, 2 and / or high N 2 atmosphere and / or high carbon active environment.
[0048] In addition, the ferritic alloys of the present disclosure can be made using solidification rates that normally occur in the range from conventional metallurgy to rapid solidification. The alloys of the present disclosure are also suitable for making all types of forged and extruded products, such as wire, strip, rod and plate. As is well known to those skilled in the art, the amount of hot and cold plastic deformation, as well as the grain structure and grain size, vary between product forms and production routes.
[0049] The functions and effects of the essential alloying elements of the alloys defined above and below will be presented in the following paragraphs.The list of functions and effects of the individual alloying elements should not be considered complete, as other functions and effects may also exist for the alloying elements.
[0050] Carbon (C)
[0051] Carbon may exist as an inevitable impurity produced by the production process. Carbon may also be included in ferritic alloys as defined above or below to improve strength by precipitation hardening. In order to have a significant effect on the strength of the alloy, carbon should be present in an amount of at least 0.01% by weight. At too high a level, carbon may cause difficulty in forming the material and also have a negative effect on corrosion resistance. Therefore, the maximum amount of carbon is 0.1% by weight. For example, the content of carbon is 0.02-0.09% by weight, such as 0.02-0.08% by weight, such as 0.02-0.07% by weight, such as 0.02-0.06% by weight, such as 0.02-0.05% by weight, such as 0.01-0.04% by weight.
[0052] Nitrogen (N)
[0053] Nitrogen may be present as an unavoidable impurity resulting from the production process. Nitrogen may also be included in ferritic alloys as defined above or below to improve strength by precipitation hardening, particularly when a powder metallurgy process route is applied. At too high a level, nitrogen may result in difficulty in alloy formation and also have a negative effect on corrosion resistance. Therefore, the maximum amount of nitrogen is 0.1 wt %. Suitable ranges for nitrogen are, for example, 0.001-0.08 wt %, for example, 0.001-0.05 wt %, for example, 0.001-0.04 wt %, for example, 0.001-0.03 wt %, for example, 0.001-0.02 wt %.
[0054] Oxygen (O)
[0055] Oxygen may be present in the alloy as defined above or below as an impurity resulting from the production process. In such case, the amount of oxygen may be up to 0.02% by weight, for example up to 0.005% by weight. If oxygen is intentionally added to provide strength by dispersion strengthening, the alloy as defined above or below contains up to or equal to 0.2% by weight of oxygen when the alloy is manufactured by a powder metallurgy process route.
[0056] Chromium (Cr)
[0057] Chromium is present in the alloy of the present disclosure primarily as a matrix solid solution element. Chromium promotes the formation of an aluminum oxide layer on the alloy by the so-called third element effect, i.e. by forming chromium oxide during a transient oxidation phase. To achieve this, chromium should be present in the alloy as defined above or below in an amount of at least 4 wt.%. In the alloy of the present disclosure, Cr also enhances the formation of brittle σ phase and Cr 3The effect appears at about 12 wt% and increases at levels above 15 wt%, so the limit for Cr is 15 wt%. Also from an oxidation point of view, contents above 15 wt% will result in an undesirable contribution of Cr to the protective oxide scale. According to one embodiment, the Cr content is 5-13 wt%, such as 5-12 wt%, such as 6-12 wt%, such as 7-11 wt%, such as 8-10 wt%.
[0058] Aluminum (Al)
[0059] Aluminum is an important element in alloys as defined above or below. When exposed to oxygen at high temperatures, aluminum forms a dense and thin oxide Al by selective oxidation. 2 O 3 , which will protect the underlying alloy surface from further oxidation. The amount of aluminum should be at least 2 weight percent to ensure the formation of a protective surface layer containing aluminum-rich oxides, and also to ensure that there is enough aluminum to repair the protective surface layer when it is damaged. However, aluminum has a negative effect on formability, and large amounts of aluminum can cause cracks to form in the alloy during its machining. Therefore, the amount of aluminum should not exceed 6 weight percent. For example, the aluminum can be 3-5 weight percent, such as 2.5-4.5 weight percent, such as 3-4 weight percent.
[0060] Silicon (Si)
[0061] In commercial FeCrAl alloys, silicon is usually present at levels up to 0.4 wt.%. In ferritic alloys as defined above or below, Si will play a very important role since it has been found to have a large effect on improving oxidation resistance and corrosion resistance. The upper limit of Si is determined by the loss of workability in hot and cold conditions and the formation of brittle Cr during long-term exposure. 3 The sensitivity of Si and the σ phase to increase is set. Therefore, the addition of Si must be carried out in relation to the content of Al and Cr. Therefore, the amount of Si is 0.5-3 wt%, such as 1-3 wt%, such as 1-2.5 wt%, such as 1.5-2.5 wt%.
[0062] Manganese (Mn)
[0063] Manganese may be present as an impurity in an alloy as defined above or below at up to 0.4 wt.-%, for example 0-0.3 wt.-%.
[0064] Yttrium (Y)
[0065] In melt metallurgy, yttrium can be added in an amount of up to 0.3% by weight to improve the adhesion of the protective surface layer. Furthermore, in powder metallurgy, if yttrium is added to produce a dispersion with oxygen and / or nitrogen, the yttrium content is an amount of at least 0.04% by weight to achieve the desired dispersion hardening effect by oxide and / or nitride. The maximum amount of yttrium present in the form of oxygen-containing yttrium compounds in dispersion hardened alloys can be up to 1.0% by weight.
[0066] Scandium (Sc), cerium (Ce), lanthanum (La), ytterbium (Yb)
[0067] Scandium, cerium, lanthanum, and ytterbium are interchangeable elements and may be added individually or in combination in a total amount up to 0.2 wt % to improve the oxidation properties, aluminum oxide (Al 2 O 3 ) layer or alloy with Al 2 O 3 Adhesion between layers.
[0068] Molybdenum (Mo) and tungsten (W)
[0069] Both molybdenum and tungsten have a positive effect on the hot strength of the alloy as defined above or below. Mo also has a positive effect on the wet corrosion properties. They can be added individually or in combination in an amount of up to 4.0 wt. %, for example 0-2.0 wt. %.
[0070] Reactive Elements (RE)
[0071] By definition, reactive elements have a high reactivity with carbon, nitrogen and oxygen. Titanium (Ti), niobium (Nb), vanadium (V), hafnium (Hf), tantalum (Ta) and thorium (Th) are reactive elements in the sense of having a high affinity for carbon, and therefore they are strong carbide formers. These elements are added to improve the oxidation properties of the alloy. The total amount of the elements is up to 3.0 wt. %, such as more than 1.0 wt. %, such as 1.5 to 2.5 wt. %.
[0072] The maximum amount of each reactive element will depend primarily on the tendency of that element to form unfavorable intermetallic phases.
[0073] Zirconium (Zr)
[0074] Zirconium is often referred to as a reactive element because it is very reactive toward oxygen, nitrogen, and carbon. In the alloys of the present disclosure, it has been found that Zr has a dual role in that it will be present in the protective surface layer containing aluminum-rich oxides to improve oxidation resistance, and also forms carbides and nitrides. Therefore, in order to achieve the best properties of the protective surface layer containing aluminum-rich oxides, it is advantageous to include Zr in the alloy.
[0075] However, Zr levels above 0.40 wt% will have an impact on oxidation due to the formation of Zr-rich intermetallic inclusions, and levels below 0.05 wt% will be too little to serve a dual purpose, regardless of the levels of C and N. Thus, if Zr is present, it ranges from 0.05-0.40 wt%, such as 0.10 to 0.35 wt%.
[0076] Furthermore, it was found that in order to achieve even better oxidation resistance of the protective surface layer, i.e. the alumina scale, the relationship between Zr and N and C may be important. Thus, the inventors have surprisingly found that if Zr is added to an alloy and the alloy also contains N and C, and if the following conditions are met (element contents are given in wt. %), the resulting alloy will achieve good oxidation resistance:
[0077] for example for example
[0078] The balance in a ferritic alloy as defined above or below is Fe and unavoidable impurities. Examples of unavoidable impurities are elements and compounds which are not intentionally added but cannot be completely avoided because they usually occur as impurities in materials used, for example, for the production of ferritic alloys.
[0079] Figure 1a and Figure 1b It shows that in Si-containing ferrite alloys, higher Cr is prone to form Si 3 Cr inclusions, while 20% Cr also tends to promote the formation of undesirable brittle σ phase after long exposure in the focus temperature region. Although only two Cr levels, 10% and 20%, are shown in the figure, the trend of increasing brittle phases with increasing Cr levels is clearly confirmed. It should be noted that at 10% Cr, there is no σ phase, while at both Cr levels at higher Si contents, Cr 3 The amount of Si phase increases. Therefore, these figures show that there is a problem when using Cr levels of about 20%.
[0080] When the term "≤" or "less than or equal to" is used in the following context "element ≤ number", the skilled person knows that the lower limit of the range is 0 wt%, unless another number is explicitly stated. Furthermore, the indefinite article "a" or "an" does not exclude a plurality.
[0081] The present disclosure is further illustrated by the following non-limiting examples.
[0082] Example
[0083] The test melt was produced in a vacuum furnace. The composition of the test melt is shown in Table 1.
[0084] The obtained samples were hot rolled and processed into flat bars with a cross section of 2 mm × 10 mm. They were then cut into 20 mm long specimens and ground to 800 mesh with SiC paper to expose to air and combustion conditions. Some bars were cut into 200 mm long × 3 mm × 12 mm bars for tensile testing in a Zwick / Roell Z100 tensile testing apparatus at room temperature.
[0085] The results of the exposure and tensile tests are shown in Table 1.
[0086] The samples were tested for yield and fracture stress and elongation at break in a standard tensile testing machine, and results giving >3% elongation at break were designated as "x" in the "machinability" column of the table. Thus, "x" indicates an alloy that is readily hot rolled and exhibits ductile properties at room temperature. In the "oxidation" column, "x" indicates that the alloy forms a protective alumina-rich oxide scale at 950°C in air and at 850°C with biomass ash deposits.
[0087] Table 1 - Composition of melts and results of tests for processability and oxidation, (x) represents values between 3% and 6% elongation.
[0088]
[0089]
[0090] Therefore, it can be seen from the above table that the alloys of the present disclosure show good processability and good oxidation resistance.
[0091] Figure 2a )to Figure 2e ) discloses a sample, wherein the sample is the present disclosure ( Figure 2a )4783 and Figure 2b Polished cross-sections of the disclosed alloys (Alloy 4779) and three comparative alloys after exposure to biomass (wood chips) ash containing a large amount of potassium at 850°C and 50 1-hour cycles. The micrographs were taken with a JEOL FEG SEM at 1000x magnification and show a clear behavioral advantage between the disclosed alloys and the reference materials. It can be seen that a 3-4 μm thin and protective alumina scale (aluminum oxide layer) has formed on the disclosed alloys, while a thicker and less protective chromium oxide (chromium oxide) rich scale is formed on stainless steel (2c-11Ni, 21Cr, N, Ce, balance Fe) and Ni-based alloys (2e-Inconel625: 58Ni, 21Cr, 0.4Al, 0.5Si, Mo, Nb, Fe), and a relatively porous and non-protective alumina scale (aluminum oxide) is formed on the comparative FeCrAl alloy (Alloy 4776). Figure 2d -20Cr, 5Al, 0.04Si, balance Fe).
[0092] from Figure 2a-2e It can be seen that the addition of Si, Al and Cr according to the ranges of the present disclosure will promote the formation of alumina scale at Al contents as low as about 2 wt % and chromium contents as low as 5 wt %.
Claims
1. A ferritic alloy, the ferritic alloy consisting of the following elements in weight % [wt %]: C 0.01 to 0.1; N: 0.001 to 0.1; O:≤0.2; Cr 4 to 15; Al 3 to 5; Si 1.5 to 2.5; Mn: ≤0.4; Mo+W: individual amount or combined amount up to 4.0; Y≤1.0; Sc, Ce, La and / or Yb: individually or in combination up to 0.2 in total; Zr: 0.10 to 0.35; RE = titanium (Ti), niobium (Nb), vanadium (V), hafnium (Hf), tantalum (Ta) and thorium (Th), in a total amount of greater than 1.0 wt% to 2.5 wt%; The balance is Fe and conventional impurities and must also satisfy the following equation (elements are expressed as weight fractions): 0.016≤(Al+0.5Si)(Cr+10Si+0.1)≤0.020, The amounts of C, N and Zr satisfy the following equation:
2. The ferrite alloy according to claim 1, wherein Cr is 5 wt % to 13 wt %.
3. A coating comprising a ferritic alloy according to any preceding claim.
4. An article comprising the ferritic alloy according to any one of claims 1 to 2.
5. Use of the ferritic alloy according to any one of claims 1 to 2 for producing coatings and / or covering layers and / or articles.
6. Use of the ferritic alloy according to any one of claims 1 to 2 for the production of articles or coatings to be used in corrosive environments.
7. Use of a ferritic alloy according to any one of claims 1 to 2 for the manufacture of articles or coatings to be used in furnaces or as heating elements.
8. Use of the ferritic alloy according to any one of claims 1 to 2 in the following environments: wherein the ferritic alloy is in contact with salts, liquid lead and other metals, in contact with ash or high carbon content deposits, combustion atmospheres, atmospheres with low pO2 and / or high N2 and / or high carbon activity.
Citation Information
Patent Citations
Apparatus and method for detecting fouled cooling circuits in a blast furnace or the like
EP0075420A1
Iron-chromium-aluminium alloy and article and method therefor
EP0091526A2
Rapidly solidified iron-chromium-aluminium alloy foil, with high oxidation resistance
EP0475420A1
Al-containing ferritic stainless steel with excellent oxidation resistance and electrical conductivity.
JP5645417B2
ferritic stainless steels
DE1932147A1